TI_GERICHTE 52.2013.360 vom 12. Januar 2015 , Licenza edilizia per interventi ad un edificio nel nucleo. Clausola estetica - TI Tribunale d'appello (2015)
Licenza edilizia per interventi ad un edificio nel nucleo. Clausola estetica